'Breaking Bad' or being good? Moral conflict and political conduct in Darjeeling/India. Issue 1 (2nd January 2018) - Wenner, Miriam
Abstract : This paper explores the effects of moral pluralism and moral conflict on political conduct and subjectivities. Challenging cultural relativist and monist positions, but going beyond a solely pragmatist reading of South Asian politics, it displays how actors navigate between conflicting roles, domains, commitments, and values. These contradictions, I argue, have a structuring effect on politics. This is not only because attempts to juggle different moral values guide political conduct, but also because moral evaluations of leaders are one constituting element of political legitimacy. I explore these effects through a case study from Darjeeling, India, where a movement for regional autonomy demanding 'virtuous' dedication from leaders and followers seems to pose a counterpoint to a perceivably 'dirty' party politics. The case shows that there is not one overarching value guiding political conduct, but that different priorities gain or lose importance over time. Far from being passive subjects forced to comply with immoral politicians, some decide to live up to their personally held principles.